Agroecological and sustainable management of school gardens - Russi, Alessandra (Electronic Journal "Fórum Ambiental da Alta Paulista", 2024)
School gardens serve as environments for learning about various topics, including agroecological cultivation, in contrast to traditional agriculture. From this perspective, a range of tools can aid in managing pests and diseases, thereby minimizing crop losses and providing alternatives to agrochemicals. This study aimed to conduct a comprehensive literature review on diverse strategies for the agroecological management of vegetables and to examine existing practices in school gardens. The goal was to propose alternative approaches for the management of arthropods and pathogenic microorganisms. The methodology involved reviewing educational materials and scientific publications addressing the ecological and sustainable management of vegetable gardens, complemented by the creation of tables for analytical and comparative purposes. The results demonstrated the availability of numerous techniques and recommendations for pest and disease management, showing promising outcomes. Additionally, some of these strategies have already been successfully implemented in school gardens. Consequently, the adoption of various agroecological tools can significantly enhance both the quantity and quality of vegetables produced in schools, fostering environmental awareness and encouraging the appreciation of ancestral knowledge integral to garden maintenance.